A Sensitive Method for Determination 1,25-Dihydroxyvitamin D3 in Human Brain using Ultra-Pressure Liquid Chromatography Tandem Mass Spectrometry - Xuan, Andrew; Dolnikowski, Gregory G; Booth, Sarah L; Shea, M Kyla; Schneider, Julie A; Fu, Xueyan (Current developments in nutrition, 2024)
The hormonally active form of vitamin D, 1,25-Dihydroxyvitamin D3 [1,25(OH)2D3], has been associated with neuroprotective effects in the brain, but has been difficult to measure in human brain tissue because of its low concentration. The aim of this study was to develop and validate a sensitive method to quantify 1,25(OH)2D3 in the human brain. Prior to analysis by the LC-MS/MS, the samples were derivatized with 4-phenyl-1,2,4-triazoline-3,5-dione. The method showed good linearity of 1,25(OH)2D3 over the physiological range (R2 = 0.9998). The limit of detection was 2.5 pg/g, >10 times lower than the previously reported limit of detection. The average 1,25(OH)2D3 concentrations in 3 regions of human brain tissue samples were: anterior watershed 30.7 pg/g; mid-temporal cortex 19.2 pg/g; and cerebellum 18.5 pg/g. This validated method to quantify 1,25(OH)2D3 in human brain tissue can be applied to obtain information about its presence in various regions of the human brain associated with neurodegenerative diseases.